Convergence of placenta biology and genetic risk for schizophrenia. (June 2018) - Ursini, Gianluca; Punzi, Giovanna; Chen, Qiang; Marenco, Stefano; Robinson, Joshua; Porcelli, Annamaria; Hamilton, Emily; Mitjans, Marina; Maddalena, Giancarlo; Begemann, Martin; Seidel, Jan; Yanamori, Hidenaga; et al.
Abstract Defining the environmental context in which genes enhance disease susceptibility can provide insight into the pathogenesis of complex disorders. We report that the intra-uterine environment modulates the association of schizophrenia with genomic risk (in this study, genome-wide association study–derived polygenic risk scores (PRSs)). In independent samples from the United States, Italy, and Germany, the liability of schizophrenia explained by PRS is more than five times greater in the presence of early-life complications (ELCs) compared with their absence. Patients with ELC histories have significantly higher PRS than patients without ELC histories, which is confirmed in additional samples from Germany and Japan. The gene set composed of schizophrenia loci that interact with ELCs is highly expressed in placenta, is differentially expressed in placentae from complicated in comparison with normal pregnancies, and is differentially upregulated in placentae from male compared with female offspring. Pathway analyses reveal that genes driving the PRS-ELC interaction are involved in cellular stress response; genes that do not drive such interaction implicate orthogonal biological processes (for example, synaptic function). We conclude that a subset of the most significant genetic variants associated with schizophrenia converge on a developmental trajectory sensitive to events that affect the placental response to stress, which may offer insights into sex biases and primary prevention. Early-life complications modulate the association of genomic risk and schizophrenia.